1996
DOI: 10.1152/ajpheart.1996.271.3.h914
|View full text |Cite
|
Sign up to set email alerts
|

Early collateral and microvascular adaptations to intestinal artery occlusion in rat

Abstract: The technique to repeatedly observe exactly the same vessels in the rat intestine was used to investigate vascular compensation during the 1st wk after abrupt arterial ligation. A collateral-dependent tissue region was created by ligation of three to four sequential intestinal arteries. At the center of the collateral-dependent region, arterial pressure decreased from 96 +/- 3.7 to 29 +/- 2.5 mmHg, and intestinal blood flow fell approximately 80% during maximal dilation initially postligation. One week later, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 0 publications
5
89
0
Order By: Relevance
“…For example, regression of medial thickness may result from the reduction in the levels of angiotensin II or the decrease in wall stress, whereas the widening of the lumen may have resulted from the increase in blood flow associated with the increase in arterial pressure following cessation of therapy. [37][38][39] An additional objective was to determine whether the depressor response or the removal of a trophic factor was the critical component in producing persistent changes in MAP and vascular structure. Two groups of SHR received the same degree of ACE inhibition and therefore a similar reduction in the trophic factor angiotensin II, with one group receiving a diet that was low in sodium.…”
Section: Discussionmentioning
confidence: 99%
“…For example, regression of medial thickness may result from the reduction in the levels of angiotensin II or the decrease in wall stress, whereas the widening of the lumen may have resulted from the increase in blood flow associated with the increase in arterial pressure following cessation of therapy. [37][38][39] An additional objective was to determine whether the depressor response or the removal of a trophic factor was the critical component in producing persistent changes in MAP and vascular structure. Two groups of SHR received the same degree of ACE inhibition and therefore a similar reduction in the trophic factor angiotensin II, with one group receiving a diet that was low in sodium.…”
Section: Discussionmentioning
confidence: 99%
“…After experimentation, animals were euthanized with an overdose of anesthetic and aortic transection. A collateral artery model (41) was created within young and mature male Wistar rats (Harlan; Indianapolis, IN) weighing ϳ200 g (ϳ2 mo old) and ϳ600 g (Ͼ8 mo old), respectively. Acute animal studies were completed with both groups for determination of blood flow and shear rate.…”
Section: Methodsmentioning
confidence: 99%
“…After laparotomy, the ileal portion of the bowel and the cecum were gently placed into a support chamber attached to the rat's abdomen and bathed in 37°C PBS. A collateral-dependent region of the bowel containing 45-55 first-order arterioles was created by the sequential ligation of 3-4 ileal arteries located near the cecum (41). This selectively increases flow in the ileal arteries immediately adjacent to the collateral-dependent region.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, similar outward remodeling has been observed in vivo (11). Increased wall shear stress, known to cause acute vasodilatation in many vascular beds (27,28), was shown by Pistea et al (36) to prevent inward remodeling in pressurized vessels in vitro and has been shown in a number of studies to cause outward remodeling in vivo (45,46). Finally, in human essential hypertension, there are indications that pharmacological normalization of the structural hypertensive changes in microvessels depend on vasodilatation (32).…”
Section: Critique Of the Modelmentioning
confidence: 70%